Trade policy formation when geography matters for specialisation - Susanna Thede (University College Dublin, UCD School of Economics, 2005)
In this paper, trade policy formation is incorporated into an economic geography model. The political setup used is a modified version of that introduced by Grossman and Helpman (1994) in which policy makers may be influenced by lobbying contributions. On the basis of the underlying trade framework, lobbying activity is performed in benefit of capital interests. Optimal policy outcomes indicate that the largest countries and countries that are disadvantaged by trade regulation favour trade liberalisation. Moreover, the optimal domestic policy is more open to trade when the local and global competition facing domestic firms is less fierce, the welfare dependency on manufacturing imports is larger and when there is a more intense preference for variety in consumption. It is shown that lobbying influence on policy is increasing in the concentration of capital ownership in the population. It is also revealed that, in the cases when domestic special and general interests do not coincide, lobbying activity is performed to liberalise trade. In addition, this actually implies that the presence of lobbying influence on policy raises the long-run national welfare.
hdl:10197/1792
Keywords: D72; F12; F13; 330; Economic Geography; International Specialisation; NationalWelfare; Lobbying Contributions; Market Access Reciprocity